Ашхабадский вор: [роман] / А. Бушков - Бушков Александр Александрович (ОЛМА Медиа Групп, 2015)
Экземпляры: Валамазская, Васильевская б-ки (20151015) / Инвентарный номер: 44988 / Цена: 118 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 94 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6